(untitled) (Tanzania Medical Journal, 2016)
Frontal-orbital Fibrous dysplasia (FD) is well documented, however, it rarely present as cystic lesion. Typically occurs in patients between the ages of 5 and 15 years. We report a case of frontal-orbital fibrous dysplasia in a 27 years old man who presented with supraorbital swelling and painless proptosis of the left eye. Computed tomography revealed a disease, mainly cystic and expansile with areas of punctuate calcification encroaching the orbit, frontal and ethmoid sinuses. The diagnosis of FD was confirmed on pathological examination. This case report includes clinical aspect and radiographic appearance. The differential diagnosis with ossifying fibroma, aneurysmal bone cyst, giant cell tumour and osteomyelitis are discussed as well.